American Indian Identity and Blood Quantum in the 21st Century: A Critical Review. (15th January 2012) - Schmidt, Ryan W.
Abstract : Identity in American Indian communities has continually been a subject of contentious debate among legal scholars, federal policy-makers, anthropologists, historians, and even within Native American society itself. As American Indians have a unique relationship with the United States, their identity has continually been redefined and reconstructed over the last century and a half. This has placed a substantial burden on definitions for legal purposes and tribal affiliation and on American Indians trying to self-identify within multiple cultural contexts. Is there an appropriate means to recognize and define just who is an American Indian? One approach has been to define identity through the use of blood quantum, a metaphorical construction for tracing individual and group ancestry. This paper will review the utility of blood quantum by examining the cultural, social, biological, and legal implications inherent in using such group membership and, further, how American Indian identity is being affected.